واقع التعليم الالكتروني خلال جائحة كورونا دراسة ميدانية لأساتذة وطلبة جامعة البصرة - Sultan, أ.م.د. حمزة جابر; Salman, م.م. بيداء داود (Tasnim International Journal for Human, Social and Legal Sciences, 2022)
This study aims to identify the reality of e-learning during the Corona pandemic. It is a field study of the professors and students of the University of Basra. The sample is chosen from the study population randomly، and the study tool is a questionnaire with closed questions.